Relación entre estilos de liderazgo y funciones ejecutivas de planificación y toma de decisiones en oficiales jefes de la Armada Argentina - Luis Marcelo Martínez; Lucas Canga (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
– The objective of this research was to analyze the relationship between leadership styles and executive functions of planning and decision-making, in chief officers of the Argentine Navy, who are working as students of the Command and General Staff course at the Naval War School. A survey was carried out where a sample of 21 chief officers of the Argentine Navy in the rank of Lieutenant Commander was analyzed, in a population of 153 qualified for command function, whose age range is between 37 and 46 years old, resulting in an average of 40.71 years and an average length of service in the force of 20.88 years, ranging between 18 and 24 years of service. This sample was made up of officers from three different ranks, naval (n = 9), naval aviators (n = 6) and marines (n = 6). The results obtained indicate the absence of correlation between the leadership styles that these officers demonstrated and the skills in the executive functions of decision-making and planning. Likewise, it was found that the values obtained from the tests carried out yielded results that allow to conclude that the chief officers of the Argentine Navy in the Lieutenant Commander hierarchy possess very high competencies in decision-making and planning, as well as oriented leadership profiles to transformational leadership. The conclusions is that these competencies are significant for the operational and tactical leadership of the means and personnel in the Argentine Navy.
Keywords: 330; leadership styles; decision making; planning; management and leadership; ArgentineNavy; estilos de liderazgo; toma de decisiones; planificación; conducción y liderazgo; Armada Argentina